2020
DOI: 10.17557/tjfc.742244
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Methods for Dry Matter Content Determination in Potato Using Multi-Environments Field Data and Stability Statistics

Abstract: Tuber dry matter content (TDM) is considered as the main determinant of processed potato tuber quality. In order to investigate rapid, practicable and reliable methods for the measurement of TDM, a study was planned to compare three standard methods (digital potato hydrometer, moisture-drying on quartz seasand and oven-dry) among 189 diverse potato genotypes, grown under three environmental conditions (Hatay "standard water application", Konya "standard water application" and Konya "drought" conditions). ANOVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The post-harvest dry matter content in tubers of the tested Satina variety, regardless of factors, averaged 152.0 and 146.9 g kg −1 for Experiment I and Experiment II, respectively (Tables 1 and 2). The varying dry matter content of tubers of edible varieties has been reported by Koch et al [38], Mystkowska [39] and Naeem and Caliskan [40], among others. According to the authors, the dry matter content of tubers, depending on the variety and the cultivation technology, can vary within very large limits from 183 g kg −1 in the study of Mystkowska [39] to 350 g kg −1 in the study of Naeem and Caliskan [40].…”
Section: Dry Mattermentioning
confidence: 73%
See 1 more Smart Citation
“…The post-harvest dry matter content in tubers of the tested Satina variety, regardless of factors, averaged 152.0 and 146.9 g kg −1 for Experiment I and Experiment II, respectively (Tables 1 and 2). The varying dry matter content of tubers of edible varieties has been reported by Koch et al [38], Mystkowska [39] and Naeem and Caliskan [40], among others. According to the authors, the dry matter content of tubers, depending on the variety and the cultivation technology, can vary within very large limits from 183 g kg −1 in the study of Mystkowska [39] to 350 g kg −1 in the study of Naeem and Caliskan [40].…”
Section: Dry Mattermentioning
confidence: 73%
“…The varying dry matter content of tubers of edible varieties has been reported by Koch et al [38], Mystkowska [39] and Naeem and Caliskan [40], among others. According to the authors, the dry matter content of tubers, depending on the variety and the cultivation technology, can vary within very large limits from 183 g kg −1 in the study of Mystkowska [39] to 350 g kg −1 in the study of Naeem and Caliskan [40]. In our study, only the application of manure in Experiment II had a significant effect on the change in dry matter content (Table 2).…”
Section: Dry Mattermentioning
confidence: 73%
“…In this regard, after using various stability measurements were able to identify 'Kuras' as a stable starch cultivar. It is also worth indicating that Naeem and Caliskan (2020) found that stability statistics depend on the method used for determining dry matter in the tubers.…”
Section: Discussionmentioning
confidence: 99%
“…Clones 9 and 10 could be chosen for this purpose. Naeem and Caliskan (2020) analysed 189 potato genotypes and reported tuber dry matter ranged from 15.19% to 34.50%. They noted that dry matter content was an early determinant of tuber quality and that it influenced the final yield of processed tuber products (chips/crisps and French fries).…”
Section: Discussionmentioning
confidence: 99%